2018
DOI: 10.1037/pro0000186
|View full text |Cite
|
Sign up to set email alerts
|

Parent preferences and experiences with psychological treatment: Results from a direct-to-consumer survey using the marketing mix framework.

Abstract: Direct-to-consumer (DTC) marketing strategies represent an increasingly popular approach to promote patient awareness of psychological treatments (PTs). The Marketing Mix is a well-established framework used to inform marketing decisions consisting of four "P's": Product (or Service), Promotion, Place, and Price. We conducted the first DTC marketing survey using the Marketing Mix framework to explore how parents concerned about their adolescents' behavioral health receive information about PTs. A sample of 411… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 30 publications
(44 reference statements)
1
38
1
Order By: Relevance
“…For example, narrative‐based health education about cervical cancer has been found to be particularly beneficial for Hispanic Mexican American women (Murphy et al, ). In addition, the use of testimonials should also be considered and tested, as this was a communication method preferred by a diverse sample of parents in DTC study by Becker, Helseth et al () on parent preferences for receiving information about psychological treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, narrative‐based health education about cervical cancer has been found to be particularly beneficial for Hispanic Mexican American women (Murphy et al, ). In addition, the use of testimonials should also be considered and tested, as this was a communication method preferred by a diverse sample of parents in DTC study by Becker, Helseth et al () on parent preferences for receiving information about psychological treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Becker et al () found that consumers of adolescent substance use treatment were unfamiliar with the concept of evidence‐based therapy and had concerns that the approach seemed inflexible. Finally, two studies found that perceptions of and preferences for information about EBMHC vary according to consumer socio‐demographic and clinical characteristics such as education, race/ethnicity, income, and a history of treatment (Becker, Helseth, Frank, Escobar, & Weeks, ; S. J. Becker, Weeks et al, ).…”
mentioning
confidence: 99%
“…Our research team has previously examined parent preferences and opinions about therapy across all four dimensions of the Marketing Mix (Becker et al, 2018; Becker, Helseth, Frank, Escobar, & Weeks, 2018; Becker, Spirito, & Vanmali, 2016). Our work focusing on the product dimension revealed that parents had limited familiarity with the concept of evidence-based therapy, had incorrect assumptions about what it means, and had unfavorable impressions of the term (Becker et al, 2016).…”
mentioning
confidence: 99%
“…There is much room for research in this area; in a recent study of U.S. adults in an online sample, only 20% could accurately define evidence-based mental health care (Mora Ringle et al, 2019). In a sample of parents concerned about their teens’ substance use, almost 70% reported wanting to hear about psychological treatments via the web (Becker, Helseth, Frank, Escobar, & Weeks, 2018), and most of these same parents also reported valuing evidence-based-practice principles (Becker, Weeks, et al, 2018). However, very little research has examined how to promote potential consumers’ engagement with information about evidence-based psychological treatments or how to best define it in terms that the public will appreciate.…”
mentioning
confidence: 99%